Address at the opening of the twenty-ninth session: The organization of charity, and the education of the children of the state - Ingram, John Kells (Statistical and Social Inquiry Society of Ireland, 1875)
The public mind seems for the present averse to the discussion of questions which divide political parties. As if over-strained by the effort necessary to carry the great measures of late years, it now shows a marked disinclination for any enterprise which would give rise to similar tension and excitement. We may be pretty sure that this temper will not be of very long duration: what it is the fashion to call "burning questions" will again arise and demand solution. But during the lull, we have an excellent opportunity of making up arrears in those branches of legislation in a special sense called social, which are apt, amidst the war of parties, to be thrown into the shade and overlooked. Of such questions, those most strongly recommended to us by feeling, as well as pressed on us by prudence at the present time, are those directly affecting the well-being of the working classes.
Read before the Society, 16 November 1875
Keywords: State Aid Charities Association of New York; London Charity Organisation Society; Primary education; Poor law; 314.15